Blood Noir - Hamilton, Laurell K. (New York : Berkley Books, 2008)
When vampire hunter Anita Blake agrees to do a favor for Jason, her werewolf lover, she becomes caught up in the middle of a scandal that makes her a pawn in an ancient vampire queen's rise to power.